Emmanuel Karagiannis, Political Islam in Central Asia: The challenge ofHizb ut-Tahrir, Routledge, Λονδίνο και Ν. Υόρκη 2010, 192 σελ - Ρούσσος, Σωτήρης (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
Δεν διατίθεται περίληψη / no abstract available